Online social support for young people: Does it recapitulate in-person social support; can it help?. (March 2017) - Cole, David A.; Nick, Elizabeth A.; Zelkowitz, Rachel L.; Roeder, Kathryn M.; Spinelli, Tawny
Abstract: As social media websites have grown in popularity, public concern about online victimization has grown as well; however, much less attention has focused on the possible beneficial effects of online social networks. If theory and research about in-person social networks pertain, then online social relationships may represent an important modern source of or vehicle for support. In a study of 231 undergraduates, three major findings emerged: (1) for people with weaker in-person social support, social media sites provide a source of social support that is less redundant of the social support they receive in person; (2) in ways that were not redundant of each other, both online and in-person social support were associated with lower levels of depression-related thoughts and feelings, and (3) the beneficial effects of online social support (like in-person social support) offset some of the adverse effects of peer victimization. The study suggests that augmenting social relations via strategic use of social media can enhance young people's social support systems in beneficial ways. Highlights: The relation between online and in-person social support was curvilinear. Social media was a less redundant source of social support for people with low levels of in-person social support. Social media was a relatively redundant source for people with high levels of in-person social support. Online and in-person social support evinced incremental advantages over and above the other. Online and in-person social support both ameliorated the pernicious effects of peer victimization.